Fundamentals of selling : customers for life through service - Futrell, Charles M. (New York, NY : McGraw-Hill/Irwin, 2014)
"Fundamentals of Selling, 13e trains readers on a detailed, yet broad, step-by-step selling process that is universal in nature. Numerous sales personnel in the industry today have commented on how this market-leading textbook reflects what they do on sales calls with prospects and customers. The goal of Fundamentals of Selling has always been to demonstrate to students the order of steps within the selling process; provide numerous examples of what should be in each step; and show how the steps within the selling process interact with one another. Combined with up-to-date content and a strong ethical focus, the 13th edition of Fundamentals of Selling teaches sales the way a mentor would: with a strong, practical focus that puts the customer first"--
"Welcome to the Thirteenth Edition of Fundamentals of Selling A megatrend in today's business world involves going to extreme efforts to meet consumer needs. Organizations cannot afford to lose customers. It is always easier to sell to a satisfied customer than an unsatisfied one. The cost of acquiring a new customer is higher than keeping a present customer. "--
Machine generated contents note: Part 1: Selling as a Profession Chapter 1: The Life, Times, and Career of the Professional SalespersonChapter 2: Relationship Marketing: Where Personal Selling FitsChapter 3: Ethics First... Then Customer RelationshipsPart 2: Preparation for Relationship Selling Chapter 4: The Psychology of Selling: Why People BuyChapter 5: Communication for Relationship Building: It's Not All TalkChapter 6: Sales Knowledge: Customers, Products, TechnologiesPart 3: The Relationship Selling Process Chapter 7: Prospecting - The Lifeblood of SellingChapter 8: Planning the Sales Call Is a MustChapter 9: Carefully Select Which Sales Presentation Method to UseChapter 10: Begin Your Presentation StrategicallyChapter 11: Elements of a Great Sales PresentationChapter 12: Welcome Your Prospect's ObjectionsChapter 13: Closing Begins the RelationshipChapter 14: Service and Follow-Up for Customer RetentionPart 4: Managing Yourself, Your Career, and OthersChapter 15: Time, Territory, and Self-Management: Keys to SuccessChapter 16: Planning, Staffing, and Training Successful SalespeopleChapter 17: Motivation, Compensation, Leadership, and Evaluation of SalespeopleAppendix A: Sales Call Role-PlaysAppendix B: Personal Selling Experiential ExercisesAppendix C: Comprehensive Sales CasesAppendix D: Selling Globally.
Includes bibliographical references (pages 603-607) and index.
Keywords: Selling; BUSINESS & ECONOMICS / Sales & Selling